Performance possibilities of the flute (Descriptive analytical study) (Al-Academy, 2018)
The nay is one of the important in stvument in Arabic music which is considered one of the oriental instruments used in the oriental music tect, and is also considered one of the basic instruments in Arabic music, It is used in many religious and mundane areas, through its expressive capabilities through which expression and conveyance of feelings to the recipient, despite their importance and role in music, and through the researcher's follow-up to this subject did not find a study on the potential capabilities of the machine. In view of the above, and given the importance of this subject at the researcher, the need arose for research to study (the potential of the flute machine)..